2005
DOI: 10.1111/j.1439-0450.2005.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Two Field Isolates and Two Vaccine Strains of Porcine Parvovirus in Foetal Organs after Experimental Infection of Pregnant Sows as Determined by Real‐time PCR

Abstract: The aim of this study was to investigate the tissue distribution of two different field isolates and two vaccine strains of porcine parvoviruses (PPV) in infected piglets after transplacental infection. The viral load in 10 different foetal organs was determined by real-time polymerase chain reaction assays with SYBR Green targeting the viral VP2 gene and the genomic c-myc gene in 12 foetuses. The viral load in foetal tissues differed greatly among the different parvoviruses. Between one virulent field isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The failure to detect PPV-infection in fetuses of groups 1, 3 and 4 [PPV-143a, PPV-IDT (MSV) and PPV-NADL-2] could be interpreted as false-negative results due to autolysis or mummification, the presence of virus-neutralizing antibodies, or low virus titres in fetuses (Belak et al, 1998;Joo et al, 1976a, b, c;Soares et al, 1999), and some studies suggest that some strains may require adaptation to cell culture (Choi et al, 1989;Mayr & Mahnel, 1964). By examining some fetuses by real-time PCR with SYBR Green (Wilhelm et al, 2005), low amounts of PPV DNA could be detected in non-mummified fetuses of groups inoculated with PPV-143a, PPV-IDT (MSV) and PPV-NADL-2, and in one mummified fetus of the group infected with PPV-NADL-2. However, high amounts of PPV-DNA were only observed in both mummified and non-mummified fetuses of the group of sows infected with PPV-27a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The failure to detect PPV-infection in fetuses of groups 1, 3 and 4 [PPV-143a, PPV-IDT (MSV) and PPV-NADL-2] could be interpreted as false-negative results due to autolysis or mummification, the presence of virus-neutralizing antibodies, or low virus titres in fetuses (Belak et al, 1998;Joo et al, 1976a, b, c;Soares et al, 1999), and some studies suggest that some strains may require adaptation to cell culture (Choi et al, 1989;Mayr & Mahnel, 1964). By examining some fetuses by real-time PCR with SYBR Green (Wilhelm et al, 2005), low amounts of PPV DNA could be detected in non-mummified fetuses of groups inoculated with PPV-143a, PPV-IDT (MSV) and PPV-NADL-2, and in one mummified fetus of the group infected with PPV-NADL-2. However, high amounts of PPV-DNA were only observed in both mummified and non-mummified fetuses of the group of sows infected with PPV-27a.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR. All mummified and non-mummified fetuses were examined by real-time PCR in an Mx3000P cycler with SYBR Green as described by Wilhelm et al (2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 PPV strains of lower virulence require a higher amount of virus for productive infection and reach lower levels of replication in the different organs/tissues of the host. 4,5 Until approximately 20 years ago PPV was considered very stable genetically and antigenically. 6,7 However, more recent studies revealed considerable genetic diversity among PPVs, comprising at least 7 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses within almost every subgroup are consistently able to cross the placental barrier and infect the embryo. They include the autonomous parvoviruses (genus Protoparvovirus) (12), e.g., minute virus of mice (MVM) (13) and porcine parvovirus (PPV) (14), the dependovirus adenoassociated virus (AAV) (15), Aleutian mink disease virus (AMDV) (16), and the erythrovirus B19 (17). Viral infection with human erythroparvovirus B19 causes fifth disease in toddlers but is frequently asymptomatic in adults.…”
mentioning
confidence: 99%